Tanggungjawab Rumah Sakit Umum Daerah TC. Hilers Maumere Terkait Praktik Pembakaran Limbah Medis Ditinjau dari Undang-Undang No. 17 Tahun 2023 Tentang Kesehatan (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze The Responsibility of the Regional General Hospital (RSUD) TC. Hilers Maumere regarding the practice of burning medical waste and to examine its conformity with the provisions of Law Number 17 of 2023 concerning Health and other regulations related to hazardous waste management. Medical waste management is an important issue because improper handling may cause environmental pollution and pose serious risks to public health. This research employs an empirical legal research method with a descriptive approach, examining how the law operates in society through field data collection and analysis of relevant legal regulations.The results show that RSUD TC. Hilers Maumere implements a waste management system that includes the separation of household waste, liquid waste, and hazardous and toxic waste (B3). Medical waste is categorized and packaged according to its type, weighed, temporarily stored in medical waste storage facilities, and then destroyed using an incinerator or transported by authorized third parties. However, the practice of burning medical waste must be strictly supervised to prevent environmental impacts and potential legal violations. Therefore, stronger supervision, compliance with medical waste management standards, and the implementation of firm legal responsibility are necessary to protect public health and environmental sustainability.